Awareness of antimicrobial resistance and appropriate handling of antibiotics by the public in Saudi Arabia: A cross-sectional study using a quiz game - Waad M. Alzahrani; Lujain S. Alkliakh; Esraa B. Alwafai; Manal F. Madani; Nima L. Hersi; Eilaaf A. Shakir; Abrar K. Thabit (Elsevier, 2024)
Objective: Public awareness of antimicrobial resistance (AMR) is essential to tackling this issue. Studies in Saudi Arabia have demonstrated insufficient AMR knowledge among the public. We aimed to indirectly raise awareness while simultaneously assessing the public's knowledge. We also assessed the factors associated with optimal knowledge and antibiotic handling. Methods: We developed an online quiz game comprising 10 questions on AMR knowledge and antibiotic handling, recording each participant's score. We collected the responses from the Saudi public using a cross-sectional study design. Results: Of the 428 participants, 68.7% were females and 42.5% were aged between 41 and 65 years; 70.1% held undergraduate degrees. Only 17.8% had a health-related major. While 83.2% had heard of AMR, the median [interquartile range] AMR knowledge score was 6 [5-7] out of 10 points. Holding a health-related major and having prior knowledge of AMR were associated with higher scores (RR, 1.28 and 1.18; 95%CI, 1.13-1.44 and 1.03-1.35; P < 0.001 and P = 0.020, respectively). Conclusion: The Saudi public demonstrated average knowledge of AMR. We recommend awareness-raising campaigns about AMR targeting the public. Innovation: We utilized an innovative approach by distributing an online questionnaire as a quiz game to fulfill two purposes: the assessment of knowledge and awareness-raising about AMR.